2015
DOI: 10.1186/s12913-015-1041-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased self-efficacy: the experience of high-intensity exercise of nursing home residents with dementia – a qualitative study

Abstract: BackgroundThere has been increasing interest in the use of non-pharmacological interventions, such as physical exercise, to improve the well-being of nursing home residents with dementia. For reasons regarding disease symptoms, persons with dementia might find it difficult to participate in exercise programs. Therefore, it is important to find ways to successfully promote regular exercise for patients in residential care. Several quantitative studies have established the positive effects of exercise on biopsyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(108 citation statements)
references
References 61 publications
5
102
0
1
Order By: Relevance
“…They realised that these activities improve their physical conditions (Chen & Li, ; Cooney et al, ; Guerin et al, ; Lindelöf et al, ; Olsen et al, ; Stathi & Simey, ) and have an enhancing effect on their cognition as well (Lindelöf et al, ; Olsen et al, ; Stathi & Simey, ). Sometimes, they recognise a positive effect on the whole body, as it “revives the body” (Chen & Li, ; Cooney et al, ; Olsen et al, ; Stathi & Simey, ). Furthermore, being physically active allows them to perceive life at the nursing home as positive.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They realised that these activities improve their physical conditions (Chen & Li, ; Cooney et al, ; Guerin et al, ; Lindelöf et al, ; Olsen et al, ; Stathi & Simey, ) and have an enhancing effect on their cognition as well (Lindelöf et al, ; Olsen et al, ; Stathi & Simey, ). Sometimes, they recognise a positive effect on the whole body, as it “revives the body” (Chen & Li, ; Cooney et al, ; Olsen et al, ; Stathi & Simey, ). Furthermore, being physically active allows them to perceive life at the nursing home as positive.…”
Section: Resultsmentioning
confidence: 99%
“…Residents view requirement for support as dependency and describe this as a worst‐case scenario (Behr et al, ; Chen & Li, ; Lindelöf et al, ; Stathi & Simey, ; Taylor et al, ). In some cases, they experience their rooms and beds as a threat (Behr et al, ; Bourret et al, ; Chen, ; Olsen et al, ; Stathi & Simey, ) and actually describe their rooms as a “prison cell” (Stathi & Simey, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in one recent qualitative study, researchers interviewed participants with dementia, and confirmed their ability to adhere to a high‐intensity functional exercise program safely, understanding the requirements, and expressing their pleasure and strength they gained from the program . Another study with a similar design also reported an increased self‐efficacy after high‐intensity exercises of nursing home residents with dementia . Hence, it would be possible and feasible for people with dementia to evaluate the applicability of an exercise program.…”
Section: Introductionmentioning
confidence: 93%